2022
DOI: 10.3390/ijms23158083
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Enhances the Anti-Cancer Efficacy of Sorafenib via Suppressing MAPK/ERK/Stat3 Axis in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) incidence, as well as related mortality, has been steadily increasing in the USA and across the globe, partly due to the lack of effective therapeutic options for advanced HCC. Though sorafenib is considered standard-of-care for advanced HCC, it only improves median survival by a few months when compared to placebo. Sorafenib is also associated with several unpleasant side effects that often lead to early abatement of therapy. Here, we investigate whether a combination regimen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Ovarian cancer is among the most lethal gynecologic malignancies due to late diagnosis and the occurrence of chemoresistance, which significantly weakens the chemotherapeutic efficiency in these patients [ 1 , 2 , 3 , 4 ]. Although metformin is widely used as a hypoglycemic agent to treat patients with type 2 diabetes mellitus and non-alcoholic fatty liver disease, this drug showed important anti-tumor activity in many types of cancer, including ovarian, breast, and endometrial cancer and uterine myomas [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. The most accepted hypothesis regarding the mechanism of action of metformin in cancer cells is that this compound is an important inhibitor of respiratory chain complex I, which oxidizes NADH generated through the Krebs cycle [ 7 , 108 ].…”
Section: Conclusion and Further Remarksmentioning
confidence: 99%
“…Ovarian cancer is among the most lethal gynecologic malignancies due to late diagnosis and the occurrence of chemoresistance, which significantly weakens the chemotherapeutic efficiency in these patients [ 1 , 2 , 3 , 4 ]. Although metformin is widely used as a hypoglycemic agent to treat patients with type 2 diabetes mellitus and non-alcoholic fatty liver disease, this drug showed important anti-tumor activity in many types of cancer, including ovarian, breast, and endometrial cancer and uterine myomas [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. The most accepted hypothesis regarding the mechanism of action of metformin in cancer cells is that this compound is an important inhibitor of respiratory chain complex I, which oxidizes NADH generated through the Krebs cycle [ 7 , 108 ].…”
Section: Conclusion and Further Remarksmentioning
confidence: 99%
“…The combination treatment also led to the downregulation of the CRAF/ERK and PI3K/AKT/mTOR pathways [ 100 ]. Siddharth et al further demonstrated that metformin and sorafenib led to a significant inhibition of HCC cell growth and induced apoptosis compared to either drug alone, suppressing the MAPK/ERK/Stat3 signaling pathway [ 101 ]. Another implicated pathway is the mTOR signaling pathway.…”
Section: Preclinical Evidence About Metformin Influence On Hcc Hallmarksmentioning
confidence: 99%
“…A key component of cancer therapy is combination therapy, a mode of care that combines two or more therapeutic drugs. Te combination of anticancer medications improves efcacy in comparison to monotherapy because it targets important pathways in a manner that is often additive or synergistic [192]. In addition to therapeutic anticancer efects including reducing tumor growth and metastatic potential, this strategy may also diminish drug resistance [79].…”
Section: Combination Therapiesmentioning
confidence: 99%